About the edge-based smoothed finite element method for the Reissner-Mindlin plate-bending problem - Hung, Nguyen Xuan; Trung, Nguyen Thoi (Vietnam Journal of Mechanics, 2009)
The paper further develops the edge-based smoothed finite element method (ES-FEM) for analysis of Reissner-Mindlin plates using triangular meshes. The bending and shearing stiffness matrices are obtained using strain smoothing technique over the smoothing domains associated with edges of elements. Transverse shear locking can be avoided with help of the discrete shear gap (DSG) method. The numerical examples show that the present ES-FEM-DSG method obtains very accurate results compared to the exact solution and other existing elements